Perumusan Strategi Rekomendasi UKM Pada Masa Pandemi Covid-19 (Studi kasus : UD Darmaji) - Albertus Daru Dewantoro; Aschensio Saogo (Performa: Media Ilmiah Teknik Industri, 2021)
AbstractUD Darmaji is one of the SMEs that accepts orders for making sandals and shoes. In the last few years, UD Darmaji has experienced a decline in production, there are several causes for the decline in production from UD Darmaji, including the lack of demand and inaccurate formulation of marketing strategies in marketing strategies. There are several methods and analyzes used, namely SWOT analysis (Strength, Weaknesses, Opportunities, Threats), IFE matrix (Internal Factor Evaluation Matrix) and EFE (External Factor Evaluation Matrix) and AHP (Analytical hierarchy process) which is used for weighting and QSPM ( Quantitative Strategic Planning Matrix) to determine what strategies to choose. The results of the analysis show that the strategy of selling online using both social media and online buying and selling sites has the highest TAS (Total Attractive Score) value of 5,614, the strategy to improve the quality of the packaging is better and more attractive, with a TAS value of 5,336, and a strategy to make the workplace more comfortable by rearranging the factory so that it looks tidier and cleaner and implementing the 5R TAS value of 5.242, which will be used as a suggestion for UD Darmaji.